2007ネン ナンキョク イガク イリョウ ワークショップ ホウコク - 大野, 義一朗; オオノ, ギイチロウ; 渡邉, 研太郎; ワタナベ, ケンタロウ; Ohno, Giichiro; Watanabe, Kentaro (2008)
P(論文) 2007年の南極医学医療ワークショップが8月25日,国立極地研究所で開催された.このワークショップの目的は我が国における南極医学医療研究の到達点を明らかにし今後の研究のあり方について討議し,次期観測隊の医学医療研究を支援することである.今年は宇宙航空研究開発機構,国立スポーツ科学研究所,大学など29施設から45人が参加し,7セッション19件の演題報告を受けて活発な討議が行われた.また中国,韓国,インドからの報告があり日本も含めアジアで越冬しているすべての国の医師が集まった.昭和基地からもテレビ会議システムを使用して発表があった.討議されたテーマは南極医学医療研究の世界の動向について,アジア各国の医学医療活動の報告と連携の模索,閉鎖隔離環境の心理学調査,南極高所医学,医学研究の倫理手続き,南極基地のレジオネラ属菌,昭和基地における遠隔医療支援システム,南極海の漁船で発生した救急患者の支援活動,乾燥地医学などであった. A workshop on Antarctic medical research and medicine 2007 was held on August 25, 2007 at the National Institute of Polar Research in Tokyo. Forty five members from 29 institutes participated in the workshop including doctors from China, Korea and India in addition to Japan. Wintering over doctors currently stationed at Syowa Station also participated in the meeting and made presentations via a telecommunication system. A partial list of the issues discussed included international trends in Antarctic medical research, Asian reports of Antarctic medical activities, high altitude medicine in Antarctica, informed consent and ethical procedure in medical research, Legionella - survey at Antarctic wintering stations, real-time tele-consultation system for Antarctic medicine, rescue operation for brain stroke patients aboard fishing vessels in the Antarctic ocean and arid land medicine. departmental bulletin paper